Touristic measures on economic socio-cultural appeal of Sade Village, Central Lombok - Taufiq Kurniawan; Dwi Ayu Setyadi; Basri, Hasan; Herman Supriadi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The subject of this study is the community-based tourism of Sade village in CentralLombok, Indonesia. As Sade is proclaimed the oldest cultural village and named thelast fortress of the Sasak tribe, the indigenous people of Sade have been practicingtourism and are widely recognized among visitors. However, this research aims toanalyze holistic aspects that CBT uses the SWOT matrix to develop the strategies tomap the sustainability of Sade. The study applies qualitative with the example ofSade Village in Central Lombok as a place of the research. The primary andsecondary data are the source of research data. In-depth interviews, documentation,and observation are the primary data. The interview is conducted among the authorsand the village stakeholders, tourism community, and locals. In contrast, thesecondary data is obtained mainly from the official website of the Indonesiangovernment in numerous sectors such as the Central Bureau of Statistics, the TourismMinistry of Indonesia, and Indonesia's Ministry of Education and Culture. Thefindings show that Sade has developed and applied long-term strategy developmentas a tourist destination. The SWOT analysis elaborating economics, social, andculture is further discussed in this article.